Clinical epidemiology and outcome of HIV‐associated talaromycosis in Guangdong, China, during 2011–2017. Issue 11 (25th December 2020) - Ying, RS; Le, T; Cai, WP; Li, YR; Luo, CB; Cao, Y; Wen, CY; Wang, SG; Ou, X; Chen, WS; Chen, SZ; Guo, PL; et al.
Abstract : Objectives: Talaromycosis is an invasive mycosis endemic to Southeast Asia. This study aimed to investigate the epidemiology, clinical features and prognostic factors of HIV‐associated talaromycosis in Guangdong, China. Methods: We retrospectively evaluated HIV patients hospitalized with histopathology‐ or culture‐confirmed talaromycosis between 2011 and 2017. Factors associated with poor prognosis were identified using logistic regression. Results: Overall, 1079 patients with HIV‐associated talaromycosis were evaluated. Both the number and prevalence of talaromycosis among HIV admissions increased from 125 and 15.7% in 2011 to 253 and 18.8% in 2017, respectively, reflecting the increase in HIV admissions. Annual admissions peaked during the rainy season between March and August. Common clinical manifestations included fever (85.6%), peripheral lymphadenopathy (72.3%), respiratory symptoms (60.8%), weight loss (49.8%), skin lesions (44.5%) and gastrointestinal symptoms (44.3%). Common laboratory abnormalities were hypoalbuminaemia (98.6%), anaemia (95.6%), elevated aspartate aminotransferase level (AST) (76.9%), elevated alkaline phosphatase level (55.8%) and thrombocytopenia (53.7%). The median CD4 count was 9 cells/μL. Talaromyces marneffei was isolated from blood and bone marrow cultures of 66.6% and 74.5% of patients, respectively. The rate increased to 86.6% when both cultures were performed concurrently. At discharge, 14% of patients showed worsening conditions or died. Leucocytosis, thrombocytopenia, elevated AST, total bilirubin, creatinine and azole monotherapy independently predicted poor prognosis. Conclusions: The incidence of HIV‐associated talaromycosis has increased in Guangdong with the high HIV burden in China. Skin lesions were seen in less than half of patients. Induction therapy with azole alone is associated with higher mortality. Findings from this study should help to improve treatment of the disease.